Establish a customer property service strategy framework - Shen, Hsu-Ming; Tu, Kung-Jen; Chiang, Ting-Yi (International Journal of Strategic Property Management, 2021)
The property management services sector in China is developing rapidly, contributing significantly to employment and income. We have made recommendations for service differentiation and low costs so that even with limited resources, property management services can distribute their services effectively, reduce unnecessary costs, and implement an optimal plan. This study helps property management service providers understand the needs and expectations of customers because it is a key factor contributing to the success of the business. Based on the consumer and service quality (SERVQUAL) theories, this study applies the fuzzy Delphi method (FDM) and the analytic hierarchy process (AHP) method to construct a quality evaluation scale for property management service companies and determine key property management service items that are valued most by customers and operators in this sector. The results show that it is feasible to determine accurately factors that are used to quantify the competitiveness of the existing market and identify improvements to ensure a win–win situation for both customers and companies in this sector.